Determinants of Serum Iron Profile in Non-Anemic Pregnant Women at Delivery: A Cross-Sectional Study at Baharloo Hospital (2022-2023) - Ghalandarpoor-Attar, Seyedeh Noushin; Ghalandarpoor-Attar, Seyedeh Mojgan; Tayebi Tafreshi, Seyyed Mohammad Mahdi; Ghorbani, Asghar (Galen Medical Journal, 2025)
Background: Iron deficiency during pregnancy poses a significant risk to maternal and fetal health, especially among anemic women whose physiological demand for iron increases drastically. This study aimed to evaluate the serum iron profile of non-anemic pregnant women at the time of delivery and to identify associated demographic and clinical factors. Materials and Methods: Conducted at Baharloo Hospital between 2022 and 2023, this cross-sectional study involved pregnant women who met the primary inclusion criteria of being non-anemic in the first and second trimesters and were admitted for scheduled labor. Serum ferritin, serum iron, and total iron-binding capacity (TIBC) were quantified, alongside comprehensive analysis of hemoglobin (HB) levels and red blood cell (RBC) indices. Data on demographic characteristics, and prenatal supplement usage were collected through medical records and analyzed using SPSS software. Results: This study of 120 pregnant women (mean age 28.85 ± 6.34 years, gestational age 39.21 ± 0.8 weeks) found that most participants regularly consumed iron (93.33%) and multivitamin supplements (81.67%), with average serum iron levels of 98.73 ± 20.7 µg/dL at 3rd trimester. Key correlations included negative associations between gestational age and maternal age (r=-0.26) and between ferritin and gestational age (r=-0.18), while hemoglobin and hematocrit levels were strongly positively correlated. Logistic regression identified lower second-trimester hemoglobin as protective against delivery-time anemia (OR=0.29), and lower second-trimester MCV significantly predicted iron-deficiency anemia (IDA) (OR=0.70), when adjusting for age, gestational age, BMI, supplements or iron usage, multiparity, and educational level. Conclusion: As iron and multivitamin supplementation did not significantly reduce anemia risk and it was basically related to second-trimester MCV and hemoglobin, higher thresholds of these markers should be assigned as the goal of anemia prevention programs for Iranian women.